Allene and Propyne Combustion in Premixed Flames: A Detailed Kinetic Modeling Study. Issue 4 (3rd May 2016) - Vourliotakis, G.; Malliotakis, Z.; Keramiotis, Ch.; Skevis, G.; Founti, M. A.
ABSTRACT: The combustion chemistry of allene and propyne is critical for the breakdown of higher hydrocarbon fuels and for molecular growth processes. Allene and propyne consumption reactions are primary sources of the key propargyl and allyl radicals, which are closely linked to benzene, polyaromatic hydrocarbons (PAHs), and soot formation paths. However, uncertainties exist concerning aspects of the C3 H4 isomers' chemistry. The article is part of an on-going effort aiming towards the optimization of a comprehensive kinetic mechanism for the high temperature combustion of small (C1–C6) hydrocarbon species. The mechanism is here validated against species data from stoichiometric and fuel-rich laminar premixed allene and propyne flames with considerable success. A critical evaluation of C3 H4 consumption pathways has been carried out and the dynamics of benzene formation and destruction are discussed.